PENINGKATAN PRESTASI BELAJAR SISWA TENTANG MAKNA DEMOKRASI PELAJARAN PKN MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF - Sugeng B.W. Leonson (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
Classroom Action Research (PTK) aims to improve student learning achievement on Civics learning material delivered by the teacher, namely by using media props in the form of pictures of the meaning of democracy. through a cooperative learning approach, it is hoped that it can re-grow student learning motivation and can improve student achievement on subject matter. Data was collected by giving written tests to students to determine the extent of students' level of understanding of the subject matter as well as from the observations of peers. Students who get a score of 70 to 100 are considered complete in learning, while students who get less than 70 grades are considered incomplete in learning. Seeing the results of Classroom Action Research (PTK) through the application of cooperative learning with the image media of the meaning of democracy, it turns out that it can re-motivate students to learn and can improve students' learning achievement on the subject matter. This can be proven from the results of improvements in cycle I and cycle II that have been implemented experiencing an increase in learning achievement, namely from the initial condition of completeness which only reached 20.83% 58.33% in the first cycle and became 83.33% in the second cycle.